A Close-run Thing? Accounting for Changing Overall Turnout in UK General Elections. Issue 1 (2nd January 2019) - Pattie, Charles; Hartman, Todd; Johnston, Ron
ABSTRACT: Turnout at UK General Elections has remained stubbornly below post-war levels in the new millennium. Between 1950 and 1997, official turnout averaged 76% and never fell below 71% (in 1997); since 2001 average turnout has been 12 percentage points lower, at 64%. We investigate several possible explanations for that decline: the lack of competitiveness in recent contests; an increase in ideological similarity between the major parties; and partisan dealignment. Although electoral competitiveness affects turnout, and in the expected directions, it cannot readily account for the sudden drop in participation after 2000. But there is evidence that aggregate levels of partisanship are important: the unusually low turnout levels since 2000 are associated with unusually low levels of partisanship, and there are signs of a 'threshold effect'.